Factors that effect customer’s revisit intention towards store atmosphere in cafe among Gen Y at Kota Bharu - Nurfarah Ain Rosli; Nurhaffiza Sham Shaimon; Nurjannahtul Husna Razali; Tan Shi Wei (2016)
The aim of this research is to identify customers’ revisiting intention towards café in Kota Bharu. In competitive market of food and beverages industry, revisit intention has been mention as an important research topic. Despite the considerable number of research on repeating visitors, it remains unclear why people are take repeat visits and what type of characteristics those hold by the repeat visitors. This research aims to identify factors influencing repeat customers among Gen Y towards café in Kota Bharu, Kelantan, Malaysia. The results of this study indicated that “sound”, “sight” and “taste” were the most important revisit attributes and motives for repeat customers to café in Kota Bharu. Concerning their perception on cafe loyalty, the study revealed that respondents were enjoy café in Kota Bharu, intent to revisit and recommended cafe as for meal purpose. For the conducting the research, quantitative research approach we used and questionnaire was distributed to collect the data through simple random sampling of 375 respondents from Gen Y in Kota Bharu. There were significant relationships between Gen Y revisiting intention towards sound(r=0.639), scent(r=0.472), sight(r=0.496) and taste(r=0.631). The findings of this study would help marketers to understand the behaviour of Gen Y that significantly influence in revisiting intention on café in Kota Bharu. Hence, this will help marketers in their marketing planning to become more competitive and can gain profit.